2020
DOI: 10.1136/bmjdrc-2020-001549
|View full text |Cite
|
Sign up to set email alerts
|

Chronic complications in patients with newly diagnosed type 2 diabetes: prevalence and related metabolic and clinical features: the Verona Newly Diagnosed Type 2 Diabetes Study (VNDS) 9

Abstract: IntroductionWe explored the presence of chronic complications in subjects with newly diagnosed type 2 diabetes referred to the Verona Diabetes Clinic. Metabolic (insulin secretion and sensitivity) and clinical features associated with complications were also investigated.Research design and methodsThe comprehensive assessment of microvascular and macrovascular complications included detailed medical history, resting ECG, ultrasonography of carotid and lower limb arteries, quantitative neurological evaluation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 31 publications
(59 reference statements)
1
36
0
1
Order By: Relevance
“…It is widely accepted that CKD is a common complication of T2DM, and diabetes is the most common cause of CKD and end-stage renal disease [9]. Furthermore, CKD often develops in the early stages of T2DM [10][11][12][13]. Our data provide further evidence that CKD is a common, early comorbidity in patients with T2DM, and was more frequent in this An epidemiological link between diabetes and development of HF is evident even in the absence of ASCVD.…”
Section: Discussionsupporting
confidence: 65%
“…It is widely accepted that CKD is a common complication of T2DM, and diabetes is the most common cause of CKD and end-stage renal disease [9]. Furthermore, CKD often develops in the early stages of T2DM [10][11][12][13]. Our data provide further evidence that CKD is a common, early comorbidity in patients with T2DM, and was more frequent in this An epidemiological link between diabetes and development of HF is evident even in the absence of ASCVD.…”
Section: Discussionsupporting
confidence: 65%
“…The VNDS enrols people with type 2 diabetes within 6 months of their diagnosis. Assessment of diabetes-related complications indicated a high variability in their presentation and progression [15,18]; the prevalence of one or more diabetes-related complications (CVD, nephropathy, DSPN, CAN, retinopathy) already present at study enrolment was found to be 49.2% [9].…”
Section: Variability Of Disease Presentation and Progressionmentioning
confidence: 99%
“…However, this pathophysiological heterogeneity is not captured by current position statements and guidelines for diagnosis and treatment of diabetes [7,8]. Differences in risk factors and pathophysiological mechanisms are thought to drive the heterogeneity in preclinical abnormalities, prevalence of comorbidities and clinical complications already seen at diagnosis of diabetes [5,9]. People with diabetes further vary in the progression of their disease and in the incidence of diabetes-related complications despite comparable glycaemic control.…”
Section: Rationale For Diabetes Reclassificationmentioning
confidence: 99%
“…Type 2 diabetes, until recently considered mainly as a disease of elderly age, is now responsible for approximately 4-5% of premature deaths ( 7 ). Approximately 50% of people with diabetes signs delayed end-organ/system damages and as many as 40% of subjects have vascular complications, both result from the silent progression of the disease before its diagnosis ( 8 ). Hyperlipidemia (elevated blood lipid/lipoprotein levels) also severely affects various age groups in wealthy Western societies.…”
Section: The Cerebral Ischemia/reperfusion Cascade and Stroke Comorbiditiesmentioning
confidence: 99%